Perbandingan Pemberian Daun Kelor dan Daun Ubi Jalar terhadap Peningkatan Produksi ASI dan Berat Badan Bayi di UPTD Puskesmas Rawat Inap Cijaku Kabupaten Lebak - Ekayanti, Ekayanti; Maesyaroh, Maesyaroh (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Exclusive breastfeeding that is still low can cause nutritional problems in toddlers. According to data from UPTD Cijaku Inpatient Health Center, Lebak Regency, exclusive breastfeeding coverage in 2023 is still low, namely 70.4%. Efforts to overcome this include improving the quality of breast milk. There are many ways that can be done to facilitate breast milk, including consuming Moringa leaves and sweet potato leaves because they contain phytosterols which can increase breast milk production. To determine the comparison of giving Moringa leaves and sweet potato leaves to increase breast milk production and baby weight at the UPTD Cijaku Inpatient Health Center, Lebak Regency in 2024. quasi-experimental with a two group pretest-posttest design. The sample was 30 respondents who were breast-feeding mothers 3 days after giving birth whose breast milk production was not smooth in March 2023, who were then divided into 2 groups so that in treatment group A (giving moringa leaves) there were 15 respondents and in treatment group B (giving sweet potato leaves) there were 15 respondents. 15 respondents using accidental sampling technique. Bivariate analysis used the Wilcoxon Signed Rank Test and the Mann-Whitney test. The research results showed the effect of giving Moringa leaves on increasing breast milk production (p value = 0.001) and baby weight (p value = 0.000). There was an effect of giving sweet potato leaves on increasing breast milk production (p value = 0.001) and baby weight (p value = 0.001). There was a difference in the effect of giving Moringa leaves and sweet potato leaves on increasing breast milk production (p value = 0.037) and baby weight (p value = 0.045). Giving Moringa leaves has a greater effect on increasing breast milk production and baby weight compared to giving sweet potato leaves. It is hoped that breastfeeding mothers can consume processed Moringa leaves and sweet potato leaves regularly during breastfeeding in order to increase breast milk production so that the mother's baby gets exclusive breast milk Keywords: Moringa Leaves, Sweet Potato Leaves, Breast Milk Production, Baby Weight  ABSTRAK Pemberian ASI eklusif yang masih rendah dapat menimbulkan masalah gizi pada balita. Menurut data dari UPTD Puskesmas Rawat Inap Cijaku Kabupaten Lebak cakupan ASI eksklusif pada tahun 2023 masih sedikit yaitu sebesar 70,4%. Upaya untuk menanggulanginya antara lain dengan meningkatkan dan kualitas ASI. Banyak cara yang dapat dilakukan untuk memperlancar ASI diantaranya konsumsi daun kelor dan daun ubi jalar karena adanya kandungan fitosterol yang dapat meningkatkan produksi ASI. Mengetahui perbandingan pemberian daun kelor dan daun ubi jalar terhadap peningkatan produksi ASI dan berat badan bayi di UPTD Puskesmas Rawat Inap Cijaku Kabupaten Lebak tahun 2024. quasi eksperiment dengan rancangan two group pretest-posttest design. Sampel adalah ibu menyusui 3 hari pasca persalinan yang produksi ASInya kurang lancar pada bulan Maret 2023 sebanyak 30 responden yang nantinya dibagi menjadi 2 kelompok sehingga pada kelompok perlakuan A (pemberian daun kelor) sebanyak 15 responden dan kelompok perlakuan B (pemberian daun ubi jalar) sebanyak 15 responden dengan tehnik accidental sampling. Analisis bivariat menggunakan uji Wilcoxon Signed Rank Test dan uji Mann-Whitney. Hasil penelitian ada pengaruh pemberian daun kelor terhadap peningkatan produksi ASI (p value = 0,001) dan berat badan bayi (p value = 0,000). Ada pengaruh pemberian daun ubi jalar terhadap peningkatan produksi ASI (p value = 0,001) dan berat badan bayi (p value = 0,001). Ada perbedaan pengaruh pemberian daun kelor dan daun ubi jalar terhadap peningkatan produksi ASI (p value = 0,037) dan berat badan bayi (p value = 0,045). Pemberian daun kelor lebih berpengaruh terhadap peningkatan produksi ASI dan berat badan bayi dibandingkan dengan pemberian daun ubi jalar. Diharapkan ibu menyusui dapat mengkonsumsi olahan daun kelor maupun daun ubi jalar secara rutin selama menyusui agar dapat meningkatkan produksi ASI sehingga bayi ibu mendapatkan ASI eksklusif. Kata Kunci: Daun Kelor, Daun Ubi Jalar, Produksi ASI, Berat Badan Bayi